Carer involvement in the assessment of personal recovery: A naturalistic study of assertive community treatment in Norway - Israel, Pravin; Ruud, Torleif; Weimand, Bente (Frontiers in Psychiatry, 2023)
Background The user and carer movements have come a long way in becoming embedded in mainstream mental health services for individuals with serious mental illness. However, implementing recovery-oriented practice continues to be plagued by an individualistic clinical focus. The carers do not feel integrated despite policies and best intentions. The implementation of Assertive Community Treatment (ACT) provided an opportunity to involve the carers and compare their assessment of personal recovery with the users. Aims The aims of this study were to examine (i) how family carers and users differed in their assessment of personal recovery, (ii) whether familial and personal relationships influenced how carers assess personal recovery of users, and (iii) if the experience of family carers with the ACT team was associated with personal recovery. Methods The naturalistic, explorative study recruited 69 users and 36 family carers from 12 Norwegian ACT teams. The users and carers assessed the user's personal recovery. Family carers also reported their experience and satisfaction with the ACT teams. Analyses included independent and paired sample T-tests and correlation analysis. Results Family carers were significantly more conservative than the users' assessment of the intrapsychic and interpersonal subscales of personal recovery. The pattern held true whether the family carers were matched to the users or part of the total sample. Lastly, there was a significant negative correlation between the family carer's experience of cooperation with the ACT team and their assessment of the user's intrapersonal process of recovery. Conclusions The results of our study were consistent with previous research on carer involvement in MHS. However, it is the first study that engaged carers and assessed personal recovery of the users of ACT services. Discrepancy between carers and users is the rule. Clinicians are encouraged to embrace the discrepancy and diversity carers bring and learn the methodology of multi-informant assessments. There also is a need to address, update, and integrate the personal, familial, and relational aspects of recovery. Modification of recovery measures such as QPR and their creative use with carers has the potential to generate valuable third-party information and to involve them meaningfully in mental health services.